2021
DOI: 10.3390/nano11092433
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Induced Twisted Bilayer Graphene Infrared Plasmon Spectrum

Abstract: In this work, we investigate the role of an external electric field in modulating the spectrum and electronic structure behavior of twisted bilayer graphene (TBG) and its physical mechanisms. Through theoretical studies, it is found that the external electric field can drive the relative positions of the conduction band and valence band to some extent. The difference of electric field strength and direction can reduce the original conduction band, and through the Fermi energy level, the band is significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Carbon nanomolecules have shown excellent applications in optoelectronics due to their strong charge mobility, and the modulation of chirality is of great signicance. [34][35][36][37] In 2019, Itami et al successfully synthesized three cycloparaphenylenes (CPP) molecules with different structures composed of paraphenyl rings through a traceless synthesis method for the rst time. 1 They nested different numbers of CPPs together in different ways to form diverse interlocking structures.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon nanomolecules have shown excellent applications in optoelectronics due to their strong charge mobility, and the modulation of chirality is of great signicance. [34][35][36][37] In 2019, Itami et al successfully synthesized three cycloparaphenylenes (CPP) molecules with different structures composed of paraphenyl rings through a traceless synthesis method for the rst time. 1 They nested different numbers of CPPs together in different ways to form diverse interlocking structures.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have demonstrated this tunability, suggesting potential applications in optical communication systems and integrated photonic circuits. [149][150][151][152] A tunable electro-optic switch was developed based on TBG strips which are proposed to excite [116] Copyright 2021, The Authors, published by Springer Nature.…”
Section: Modulators and Switchesmentioning
confidence: 99%
“…The external electric field (EEF) is an important factor affecting the performance of chemical systems [18][19][20]. However, as no studies have been conducted on the structure-function relationship of [6,6]CNB under EEFs, an investigation concerning the configuration and optoelectronic properties of [6,6]CNB under EEFs is necessary.…”
Section: Introductionmentioning
confidence: 99%